1999
DOI: 10.1093/emboj/18.9.2394
|View full text |Cite
|
Sign up to set email alerts
|

An impaired routing of wild-type aquaporin-2 after tetramerization with an aquaporin-2 mutant explains dominant nephrogenic diabetes insipidus

Abstract: Autosomal recessive and dominant nephrogenic diabetes insipidus (NDI), a disease in which the kidney is unable to concentrate urine in response to vasopressin, are caused by mutations in the aquaporin-2 (AQP2) gene. Missense AQP2 proteins in recessive NDI have been shown to be retarded in the endoplasmic reticulum, whereas AQP2-E258K, an AQP2 mutant in dominant NDI, was retained in the Golgi complex. In this study, we identified the molecular mechanisms underlying recessive and dominant NDI. Sucrose gradient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
190
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 196 publications
(204 citation statements)
references
References 42 publications
13
190
0
1
Order By: Relevance
“…29 In the present study we confirm the Golgi localization of E258K AQP2 by using double confocal immunofluorescence to detect the Golgi marker mannosidase II. However, by using additional double confocal immunofluorescence microscopy to detect the late endosome/ lysosome marker LAMP 1, co-distribution of E258K AQP2 with LAMP 1 could be unequivocally demonstrated in the clone 9 hepatocytes.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…29 In the present study we confirm the Golgi localization of E258K AQP2 by using double confocal immunofluorescence to detect the Golgi marker mannosidase II. However, by using additional double confocal immunofluorescence microscopy to detect the late endosome/ lysosome marker LAMP 1, co-distribution of E258K AQP2 with LAMP 1 could be unequivocally demonstrated in the clone 9 hepatocytes.…”
Section: Discussionsupporting
confidence: 74%
“…The reason was that mixed tetramer formation between wt and E258K AQP2 has been reported that resulted in the retention of the wt protein and causing dominant NDI. 24,29 As shown in Figure 2B, AQP9 RNA was undetectable in clone 9 hepatocytes in contrast to rat liver. Thus, the possible formation of mixed tetramers composed of wt AQP9 and E258K AQP2 can be excluded.…”
Section: Stable Expression Of Wild-type and Mutant Aqp2 In Clone 9 Ramentioning
confidence: 83%
“…Miscellaneous Methods-Methods for cRNA injection in Xenopus oocytes, water permeability measurements, immunofluorescence microscopy, cell surface biotinylation, and velocity gradient centrifugation have been described previously (17,19,28). Confocal laser scanning immunofluorescence microscopy of MDCK cells was done as described previously (29).…”
Section: Methodsmentioning
confidence: 99%
“…AQP2 was detected by immunoprecipitation of the gradient fractions and quantitated by phosphorimaging. Previous studies validated this method to separate AQP2 monomers and tetramers (19). Already after 30 min of labeling, most of AQP2 distributed in the high density fractions of the gradient, corresponding to a position where tetrameric AQP2 sediments.…”
Section: Aqp2 Cellsmentioning
confidence: 95%
See 1 more Smart Citation